Assessment of PhD Research and Evaluation Program: Insights from the Graduate Tracer Study - Joje Mar P. Sanchez; Jo Ann M. Petancio; Marchee T. Picardal; Chery B. Fernandez; Helen B. Boholano; Remedios C. Bacus; Michelle Mae J. Olvido; Venus M. Cortes (Journal Evaluation in Education (JEE), 2024)
Purpose of the study: The study assessed the effectiveness of the PhD in Research and Evaluation (PhD RE) program in a state university in Central Visayas, Philippines by examining the career trajectories and competencies of its graduates from 2017 to 2024. Methodology: The study utilized a mixed-methods approach, employing online surveys and open-ended questionnaires distributed through Google Forms. Descriptive statistics was used to analyzed quantitative data, while Braun and Clarke’s thematic analysis was used for qualitative data. Main Findings: The main findings indicate that PhD RE graduates excel in research, instruction, and leadership, with most achieving professional advancement. Employers provided positive feedback, highlighting the graduates’ critical thinking, problem-solving, and research capabilities. Novelty/Originality of this study: This study is novel in that it focuses on PhD graduates in Research and Evaluation and offers fresh perspectives on how the degree affects research competencies and career advancement. The study advances understanding on doctorate programs by outlining the need for more mentoring and interdisciplinary collaboration and making recommendations for curriculum enhancements.